# 4 1 a b y 1 y 2 1 1 0 1 x 2 1 c 1 2 d y y 1 1 2 2 1 x

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 20 10 x -30 -20 -10 -10 10 20 x 30 —2 4 -20 —1 —1 -30 35. Plot f (x) on [−10, 10]; then on [−1, 0], [−0.7, −0.6], [−0.65, −0.64], [−0.646, −0.645]; for the other root use [4, 5], [4.6, 4.7], [4.64, 4.65], [4.645, 4.646]; roots −0.6455, 4.6455. 36. Plot f (x) on [−10, 10]; then on [−4, −3], [−3.7, −3.6], [−3.61, −3.60], [−3.606, −3.605]; for the other root use [3, 4], [3.6, 3.7], [3.60, 3.61], [3.605, 3.606]; roots 3.6055, −3.6055. EXERCISE SET 1.4 1. (a) (b) y -1 y 2 1 1 0 1 x 2 -1 (c) 1 2 (d) y y 1 -1 2. 2 1 x 2 -4 y (a) -2 2 1 x -2 2 y 3 y (d) 1 1 x 2 -1 x 2 y (b) x -2 (c) x 3 3 x -1 1 Exercise Set 1.4 3. 12 (a) y (b) 1 y 1 -2 -1 1 2 x -0.5 0.5 1 1.5 1 2 3 x -1 -1 (c) (d) y y 1 1 -1 1 2 3 x -1 x -1 -1 4. 5. Translate right 2 units, and up one unit. y y 1 -2 x 2 10 -2 6. Translate left 1 unit, reﬂect over x-axis, and translate up 2 units. 7. y 2 4 6 x Translate left 1 unit, stretch vertically by a factor of 2, reﬂect over x-axis, translate down 3 units. y -8 -6 -4 -2 2 4 6 x -20 x -40 1 -60 -80 –2 -100 8. Translate right 3 units, compress vertically by a factor of 1 , and translate up 2 units. 2 9. y = (x + 3)2 − 9; translate left 3 units and down 9 units. y y 15 10 5 -8 2 -6 -4 -2 2 -5 4 x x 13 10. Chapter 1 y = (x + 3)2 − 19; translate left 3 units and down 19 units. 11. y = −(x − 1)2 + 2; translate right 1 unit, reﬂect over x-axis, translate up 2 units. y y –4 x 2 x –5 -2 -1 1 2 3 4 -2 -4 -6 12. y = 1 [(x − 1)2 + 2]; translate left 1 unit 2 and up 2 units, compress vertically by a factor of 1 . 2 13. Translate left 1 unit, reﬂect over x-axis, translate up 3 units. y y 2 1 2 1 2 4 6 8 10 12 x x 1 14. Translate right 4 units and up 1 unit. 15. Compress vertically by a factor of 1 , 2 translate up 1 unit. y y 2 4 1 4 x 10 1 16. Stretch vertically by a factor of reﬂect over x-axis. √ 3 and 17. 2 3 x Translate right 3 units. y 10 y 2 x -1 2 -10 4 6 x Exercise Set 1.4 18. 14 Translate right 1 unit and reﬂect over x-axis. 19. Translate left 1 unit, reﬂect over x-axis, translate up 2 units. y y 12 10 8 6 4 2 2 x -2 2 -4 -3 -2 -1 -4 20. y = 1 − 1/x; reﬂect over x-axis, translate up 1 unit. 21. 1 -2 -4 -6 -8 x 2 Translate left 2 units and down 2 units. y y 5 -4 -2 x 2 x -2 -5 22. Translate right 3 units, reﬂect over x-axis, translate up 1 unit. 23. Stretch vertically by a factor of 2, translate right 1 unit and up 1 unit. y y 1 4 x 5 -1 2 x 2 24. y = |x − 2|; translate right 2 units. 25. Stretch vertically by a factor of 2, reﬂect over x-axis, translate up 2 units. y y 2 4 1 3 2 x 2 4 1 -2 2 -1 x 15 26. Chapter 1 Translate right 2 units and down 3 units. 27. Translate left 1 unit and up 2 units. y y x 2 3 2 –2 1 x -3 28. -2 -1 1 Translate right 2 units, reﬂect over x-axis. y 1 x 4 –1 29. y (a) (b) y = 2 0 if x ≤ 0 2x if 0 < x x -1 30. 1 y x 2 –5 31. x2 + 2x + 1, all x; 2x − x2 − 1, all x; 2x3 + 2x, all x; 2x/(x2 + 1), all x 32. 3x − 2 + |x|, all x; 3x − 2 − |x|, all x; 3x|x| − 2|x|, all x; (3x − 2)/|x|, all x = 0 33. √ √ 3 x − 1, x ≥ 1; x − 1, x ≥ 1; 2x − 2, x ≥ 1; 2, x > 1 34. (2x2 + 1)/x(x2 + 1), all x = 0; −1/x(x2 + 1), all x = 0; 1/(x2 + 1), all x = 0; x2 /(x2 + 1), all x = 0 35. (a) 3 (b) 9 (c) 2 (d) 2 36. (a) π − 1 (b) 0 (c) −π 2 + 3π − 1 (d) 1 Exercise Set 1.4 16 38. (a) t4 + 1 (b) t2 + 4t + 5 (c) x2 + 4x + 5 (e) x2 + 2xh + h2 + 1 37. (f ) x2 + 1 (g) x + 1 (a) (e) √ √ 4 5s + 2 (b) x √ √ (c) 3 5x √ (g) 1/ 4 x x+2 (f ) 0 1 +1 x2 (h) 9x2 + 1 (d) √ (d) 1/ x (h) |x − 1| 39. 2x2 − 2x +1, all x; 4x2 +2x, all x 41. 1 − x, x ≤ 1; 43. 1 1 1 1 , x = , 1; − − , x = 0, 1 1 − 2x 2 2x 2 44. 45. x−6 + 1 46. 47. (a) g (x) = 48. (a) g (x) = x + 1, h(x) = x2 (b) g (x) = 1/x, h(x) = x − 3 49. (a) g (x) = x2 , h(x) = sin x (b) g (x) = 3/x, h(x) = 5 + cos x 50. (a) g (x) = 3 sin x, h(x) = x2 (b) g (x) = 3x2 + 4x, h(x) = sin x 51. (a) f (x) = x3 , g (x) = 1 + sin x, h(x) = x2 (b) f (x) = 52. (a) f (x) = 1/x, g (x) = 1 − x, h(x) = x2 (b) f (x) = |x|, g (x) = 5 + x, h(x) = 2x 53. √ √ 1 − x2 , |x| ≤ 1 40. 2 − x6 , all x; −x6 + 6x4 − 12x2 + 8, all x 42. x2 x2 + 3 − 3, |x| ≥ x 1 , x = 0; + x, x = 0 +1 x x x+1 54. 1 -1 1 2 3 x -1 -2 -3 -4 55. Note that f (g (−x)) = f (−g (x)) = f (g (x)), so f (g (x)) is even. y f ( g(x)) 1 –3 1 –1 –1 –3 x √ {−2, −1, 0, 1, 2, 3} 2 -3 -2 √√ 6; x, x ≥ 3 (b) g (x) = |x|, h(x) = x2 − 3x + 5 x, h(x) = x + 2 y √ x, g (x) = 1 − x, h(x) = √ 3 x 17 56. Chapter 1 Note that g (f (−x)) = g (f (x)), so g (f (x)) is even. y 3 g( f (x)) 1 x –3 1 –1 3 –1 –2 57. f (g (x)) = 0 when g (x) = ±2, so x = ±1.4; g (f (x)) = 0 when f (x) = 0, so x = ±2. 58. f (g (x)) = 0 at x = −1 and g (f (x)) = 0 at x = −1 59. 6xh + 3h2 3(x + h)2 − 5 − (3x2 − 5) = = 6x + 3h h h 60. 2xh + h2 + 6h (x + h)2 + 6(x + h) − (x2 + 6x) = = 2x + h + 6 h h 61. 1/(x + h) − 1/x x − (x + h) −1 = = h xh(x + h) x(x + h) 62. 1/(x + h)2 − 1/x2 x2 − (x + h)2 2x + h =2 =− 2 h x h(x + h)2 x (x + h)2 63. (a) the origin 64. (a) (b) the x-axis (c) the y -axis (b) y (c) y x 65. (a) 66. x f (x) (a) −3 1 −2 −5 (d)...
View Full Document

## This document was uploaded on 02/23/2014 for the course MANAGMENT 2201 at University of Michigan.

Ask a homework question - tutors are online